Gas reticulation system design for Universiti Malaysia Pahang Gambang campus - Shafiq Afif, Ariff (2008)
The main objective of this project is to design a distribution system for natural gas and LPG to the facilities in Universiti Malaysia Pahang (UMP). This system will be designed to take into account of the potential use of natural gas and LPG in UMP such as for combine heat power (CHP) unit, air conditioning, and gas consumption unit. Gas either natural gas and LPG are direct source of energy which is more cost effective as compared to electricity per unit of energy value utilized. UMP is a small campus with approximately consists of 4000 students. The location of UMP is near to the transmission line or gas source and also next to future bio based industrial development. With the existing transmission line in PGU 1 and the nearest city gate in Gambang, it is a convenient way to tap the natural gas from city gate to Universiti Malaysia Pahang. In UMP also has gas engineering lab that require natural gas and LPG as feed fuel for it equipments to operate. The objectives of study are to design a utilization system and to analyze the feasibility of the system to achieve the overall target decided earlier. The electricity bill is higher which consumed by air conditioner in lab, classrooms, offices, and etc. Thus, there is a need to identify alternative energy source to plant campus that is cheaper, safe, and efficient. It is also to set benchmark or working example of an energy efficient system. The scopes of this project are to design the reticulation system, to determine the gas consumption and demand, and to calculate the cost of this project which specific for piping cost and construction. The method that been used are to calculate all the piping size and gas load demand by using certain formula according to standard such as MS930 and ASME B31.8. Gapis Software is to verify the manual calculation that already made either correct or not.-Author